Analysis of New Functional Profiles of Protein Isoforms Yielded by Ds Exonization in Rice. (January 2013) - Chien, Ting-Ying; Liu, Li-yu Daisy; Charng, Yuh-Chyang
Insertion of transposable elements (TEs) into introns can lead to their activation as alternatively spliced cassette exons, an event called exonization. Exonization can enrich the complexity of transcriptomes and proteomes. Previously, we performed a genome-wide computational analysis of Ds exonization events in the monocot Oryza sativa (rice). The insertion patterns of Ds increased the number of transcripts and subsequent protein isoforms, which were determined as interior and C-terminal variants. In this study, these variants were scanned with the PROSITE database in order to identify new functional profiles (domains) that were referred to their reference proteins. The new profiles of the variants were expected to be beneficial for a selective advantage and more than 70% variants achieved this. The new functional profiles could be contributed by an exon–intron junction, an intron alone, an intron–TE junction, or a TE alone. A Ds -inserted intron may yield 167 new profiles on average, while some cases can yield thousands of new profiles, of which C-terminal variants were in major. Additionally, more than 90% of the TE-inserted genes were found to gain novel functional profiles in each intron via exonization. Therefore, new functional profiles yielded by the exonization may occur in many local regions of the reference protein.